The Art of Goodbye: A Closer Look at Emerging Trends in End-of-Life Rituals - Lynda M Spence (EDIS)
Each year in a diverse United States, 2.5 million people die (CDC). Naturally, a one-size-fits-all final goodbye does not exist. Compounded by increased access to information, survivors as consumers are increasingly seeking alternatives to the conventional funeral. For some, tradition continues to inform, but for others, options and choices are evolving and have become a new normal.